2017
DOI: 10.1175/jamc-d-17-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rain Types and Their Z–R Relationships at Different Locations in the High Andes of Southern Ecuador

Abstract: Information on the spatiotemporal rainfall occurrence, its microphysical characteristics, and its reflectivity–rainfall (Z–R) relations required to provide rainfall mapping based on rain radar data is limited for tropical high mountains. Therefore, this study aims to analyze rainfall types in the Andes cordillera to derive different rain-type Z–R relations using disdrometer observations at three study sites representative for different geographic positions and elevations (2610, 3626, and 3773 m MSL). Rain cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 72 publications
3
51
2
Order By: Relevance
“…With the two year MRR datasets from Cuenca and Huaraz, we were able to analyze the occurrence and duration of precipitation events, as well as the temporal evolution of precipitation with respect to rain rates, radar reflectivities, fall velocities, and drop size distributions. The number and durations of the events in Cuenca are consistent with the study from Orellana-Alvear et al [14], who analyzed these parameters using disdrometer data from March 2015 to August 2016. Our results also show that both sites have more events with higher precipitation intensity during the daytime.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…With the two year MRR datasets from Cuenca and Huaraz, we were able to analyze the occurrence and duration of precipitation events, as well as the temporal evolution of precipitation with respect to rain rates, radar reflectivities, fall velocities, and drop size distributions. The number and durations of the events in Cuenca are consistent with the study from Orellana-Alvear et al [14], who analyzed these parameters using disdrometer data from March 2015 to August 2016. Our results also show that both sites have more events with higher precipitation intensity during the daytime.…”
Section: Discussionsupporting
confidence: 87%
“…The climate is characterized by a bimodal rainfall pattern with two wet seasons (MAM and SON). Cuenca has a mean annual precipitation of 969 mm [14] and a mean temperature of 14 • C [29].…”
Section: Study Areamentioning
confidence: 99%
“…As a result, convective and orographic cloud formations occurs [31]. Although precipitation (in terms of volume) mainly falls as drizzle (≈1 mm/h), higher intensity events are also experienced in the catchment (up to 140 mm/h) [32,33].…”
Section: Study Area and Datasetmentioning
confidence: 99%
“…Equations (13) and (14) were used for retrieving D 0 and N w from the observed Z H and Z DR . Equation (15) was used for classification: If the retrieved logN w is greater (smaller) than that given by this equation, the pixel is assigned as convective (stratiform) rain (hereafter the DSD-based method).…”
Section: Classifications Of Precipitation Types Using Disdrometer Andmentioning
confidence: 99%
“…Alvear et al [13] derived different rain-type Z-R relations using disdrometer data observed at three different geographic and height based on mean drop volume diameter thresholds in the high Andes of southern Ecuador. Alvear et al [14] proposed random forest model (FM) to get more accurate rainfall amounts using X-band radar installed on the highest mountain in the world.…”
Section: Introductionmentioning
confidence: 99%